Analysis of Monoclonal Antibody Sequence and Post-translational Modifications by Time-controlled Proteolysis and Tandem Mass Spectrometry - Zhang, Lichao (The American Society for Biochemistry and Molecular Biology, 2016)

(untitled) (Mol Cell Proteomics)
Methodology for sequence analysis of ∼150 kDa monoclonal antibodies (mAb), including location of post-translational modifications and disulfide bonds, is described. Limited digestion of fully denatured (reduced and alkylated) antibody was accomplished in seconds by flowing a sample in 8 m urea at a controlled flow rate through a micro column reactor containing immobilized aspergillopepsin I. The resulting product mixture containing 3–9 kDa peptides was then fractionated by capillary column liquid chromatography and analyzed on-line by both electron-transfer dissociation and collisionally activated dissociation mass spectrometry (MS). This approach enabled identification of peptides that cover the complete sequence of a murine mAb. With customized tandem MS and ProSightPC Biomarker search, we verified 95% amino acid residues of this mAb and identified numerous post-translational modifications (oxidized methionine, pyroglutamylation, deamidation of Asn, and several forms of N-linked glycosylation). For disulfide bond location, native mAb is subjected to the same procedure but with longer digestion times controlled by sample flow rate through the micro column reactor. Release of disulfide containing peptides from accessible regions of the folded antibody occurs with short digestion times. Release of those in the interior of the molecule requires longer digestion times. The identity of two peptides connected by a disulfide bond is determined using a combination of electron-transfer dissociation and ion–ion proton transfer chemistry to read the two N-terminal and two C-terminal sequences of the connected peptides.